Difference between revisions of "Chain Rule"

From Grad Wiki
Jump to navigation Jump to search
 
(8 intermediate revisions by the same user not shown)
Line 4: Line 4:
 
But, what about more complicated functions?  
 
But, what about more complicated functions?  
  
For example, &nbsp;<math>f(x)=\sin(3x)</math>&nbsp; or &nbsp;<math>g(x)=(x+1)^8?</math>
+
For example, &nbsp;<math style="vertical-align: -5px">f(x)=\sin(3x)</math>&nbsp; or &nbsp;<math style="vertical-align: -5px">g(x)=(x+1)^8?</math>
  
 
Well, the key to calculating the derivatives of these functions is to recognize that these functions are compositions.  
 
Well, the key to calculating the derivatives of these functions is to recognize that these functions are compositions.  
  
For &nbsp;<math>f(x)=\sin(3x),</math>&nbsp; it is the composition of the function &nbsp;<math>y=3x</math>&nbsp; with &nbsp;<math>y=\sin(x).</math>
+
For &nbsp;<math style="vertical-align: -5px">f(x)=\sin(3x),</math>&nbsp; it is the composition of the function &nbsp;<math style="vertical-align: -4px">y=3x</math>&nbsp; with &nbsp;<math style="vertical-align: -5px">y=\sin(x).</math>
  
Similarly, for &nbsp;<math>g(x)=(x+1)^8,</math>&nbsp; it is the composition of &nbsp;<math>y=x+1</math>&nbsp; and &nbsp;<math>y=x^8.</math>
+
Similarly, for &nbsp;<math style="vertical-align: -5px">g(x)=(x+1)^8,</math>&nbsp; it is the composition of &nbsp;<math style="vertical-align: -5px">y=x+1</math>&nbsp; and &nbsp;<math style="vertical-align: -5px">y=x^8.</math>
  
 
So, how do we take the derivative of compositions?
 
So, how do we take the derivative of compositions?
Line 18: Line 18:
 
'''Chain Rule'''
 
'''Chain Rule'''
  
Let &nbsp;<math>y=f(u)</math>&nbsp; be a differentiable function of &nbsp;<math>u</math>&nbsp; and let &nbsp;<math>u=g(x)</math>&nbsp; be a differentiable function of &nbsp;<math>x.</math>&nbsp;  
+
Let &nbsp;<math style="vertical-align: -6px">y=f(u)</math>&nbsp; be a differentiable function of &nbsp;<math style="vertical-align: -1px">u</math>&nbsp; and let &nbsp;<math style="vertical-align: -6px">u=g(x)</math>&nbsp; be a differentiable function of &nbsp;<math style="vertical-align: -1px">x.</math>&nbsp;  
  
Then, &nbsp;<math>y=f(g(x))</math>&nbsp; is a differentiable function of &nbsp;<math>x</math>&nbsp; and  
+
Then, &nbsp;<math style="vertical-align: -5px">y=f\circ g(x))</math>&nbsp; is a differentiable function of &nbsp;<math style="vertical-align: 0px">x</math>&nbsp; and  
  
::<math>y'=f'(g(x))\cdot g'(x).</math>
+
::<math>y'=(f'\circ g(x))\cdot g'(x).</math>
 
 
 
 
 
 
Taking the derivatives of <em>simple functions</em> (i.e. polynomials) is easy using the power rule.
 
 
 
For example, if &nbsp;<math style="vertical-align: -5px">f(x)=x^3+2x^2+5x+3,</math>&nbsp; then &nbsp;<math style="vertical-align: -5px">f'(x)=3x^2+4x+5.</math>
 
 
 
But, what about more <em>complicated functions</em>?
 
 
 
For example, what is &nbsp;<math style="vertical-align: -5px">f'(x)</math>&nbsp; when &nbsp;<math style="vertical-align: -5px">f(x)=\sin x \cos x?</math>
 
 
 
Or what about &nbsp;<math style="vertical-align: -5px">g'(x)</math>&nbsp; when &nbsp;<math style="vertical-align: -15px">g(x)=\frac{x}{x+1}?</math>
 
 
 
Notice &nbsp;<math style="vertical-align: -5px">f(x)</math>&nbsp; is a product, and &nbsp;<math style="vertical-align: -5px">g(x)</math>&nbsp; is a quotient. So, to answer the question of how to calculate these derivatives, we look to the Product Rule and the Quotient Rule. The Product Rule and the Quotient Rule give us formulas for calculating these derivatives.
 
 
 
'''Product Rule'''
 
 
 
Let &nbsp;<math style="vertical-align: -5px">h(x)=f(x)g(x).</math>&nbsp; Then,
 
 
 
::<math>h'(x)=f(x)g'(x)+f'(x)g(x).</math>
 
 
 
'''Quotient Rule'''
 
 
 
Let &nbsp;<math style="vertical-align: -19px">h(x)=\frac{f(x)}{g(x)}.</math>&nbsp; Then,
 
 
 
::<math>h'(x)=\frac{g(x)f'(x)-f(x)g'(x)}{(g(x))^2}.</math>
 
  
 
==Warm-Up==
 
==Warm-Up==
Calculate &nbsp;<math style="vertical-align: -5px">f'(x).</math>
+
Calculate &nbsp;<math style="vertical-align: -5px">h'(x).</math>
  
'''1)''' &nbsp; <math style="vertical-align: -7px">f(x)=(x^2+x+1)(x^3+2x^2+4)</math>
+
'''1)''' &nbsp; <math style="vertical-align: -7px">h(x)=\sin(3x)</math>
  
 
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Solution: &nbsp;
 
!Solution: &nbsp;
 
|-
 
|-
|Using the Product Rule, we have
+
|Let &nbsp;<math style="vertical-align: -5px">f(x)=\sin (x)</math>&nbsp; and &nbsp;<math style="vertical-align: -5px">g(x)=3x.</math>
|-
 
|
 
::<math>f'(x)=(x^2+x+1)(x^3+2x^2+4)'+(x^2+x+1)'(x^3+2x^2+4).</math>  
 
 
|-
 
|-
|Then, using the Power Rule, we have
+
|Then, &nbsp;<math style="vertical-align: -5px">f'(x)=\cos(x)</math>&nbsp; and &nbsp;<math style="vertical-align: -5px">g'(x)=3.</math>
 
|-
 
|-
|
+
|Now, &nbsp;<math style="vertical-align: -6px">h(x)=f\circ g(x).</math>
::<math>f'(x)=(x^2+x+1)(3x^2+4x)+(2x+1)(x^3+2x^2+4).</math>
 
 
|-
 
|-
|-
+
|Using the Chain Rule, we have
|<u>NOTE:</u> It is not necessary to use the Product Rule to calculate the derivative of this function.
 
|-
 
|You can distribute the terms and then use the Power Rule.
 
|-
 
|In this case, we have
 
 
|-
 
|-
 
|
 
|
 
::<math>\begin{array}{rcl}
 
::<math>\begin{array}{rcl}
\displaystyle{f(x)} & = & \displaystyle{(x^2+x+1)(x^3+2x^2+4)}\\
+
\displaystyle{h'(x)} & = & \displaystyle{(f'\circ g(x))\cdot g'(x)}\\
 
&&\\
 
&&\\
& = & \displaystyle{x^2(x^3+2x^2+4)+x(x^3+2x^2+4)+1(x^3+2x^2+4)}\\
+
& = & \displaystyle{\cos (3x)\cdot 3}\\
 
&&\\
 
&&\\
& = & \displaystyle{x^5+2x^4+4x^2+x^4+2x^3+4x+x^3+2x^2+4} \\
+
& = & \displaystyle{3\cos (3x).}
&&\\
 
& = & \displaystyle{x^5+3x^4+3x^3+6x^2+4x+4.}
 
 
\end{array}</math>
 
\end{array}</math>
|-
 
|Now, using the Power Rule, we get
 
|-
 
|
 
::<math>f'(x)=5x^4+12x^3+9x^2+12x+4.</math>
 
|-
 
|In general, calculating derivatives in this way is tedious. It would be better to use the Product Rule.
 
 
|}
 
|}
  
Line 97: Line 53:
 
!Final Answer: &nbsp;
 
!Final Answer: &nbsp;
 
|-
 
|-
|&nbsp; &nbsp; &nbsp; &nbsp;<math>f'(x)=(x^2+x+1)(3x^2+4x)+(2x+1)(x^3+2x^2+4)</math>
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math>h'(x)=3\cos (3x)</math>
|-
 
|or equivalently
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp;<math>f'(x)=x^5+3x^4+3x^3+6x^2+4x+4</math>
 
 
|}
 
|}
  
'''2)''' &nbsp; <math style="vertical-align: -14px">f(x)=\frac{x^2+x^3}{x}</math>
+
'''2)''' &nbsp; <math style="vertical-align: -7px">h(x)=(x+1)^8</math>
  
 
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Solution: &nbsp;
 
!Solution: &nbsp;
 
|-
 
|-
|
+
|Let &nbsp;<math style="vertical-align: -5px">f(x)=x^8</math>&nbsp; and &nbsp;<math style="vertical-align: -5px">g(x)=x+1.</math>
Using the Quotient Rule, we have
 
 
|-
 
|-
|
+
|Then, &nbsp;<math style="vertical-align: -5px">f'(x)=8x^7</math>&nbsp; and &nbsp;<math style="vertical-align: -5px">g'(x)=1.</math>
::<math>f'(x)=\frac{x(x^2+x^3)'-(x^2+x^3)(x)'}{x^2}.</math>
 
 
|-
 
|-
|Then, using the Power Rule, we have
+
|Now, &nbsp;<math style="vertical-align: -6px">h(x)=f\circ g(x).</math>
 
|-
 
|-
|
+
|Using the Chain Rule, we have
::<math>f'(x)=\frac{x(2x+3x^2)-(x^2+x^3)(1)}{x^2}.</math>
 
|-
 
|<u>NOTE:</u> It is not necessary to use the Quotient Rule to calculate the derivative of this function.
 
|-
 
|You can divide and then use the Power Rule.
 
|-
 
|In this case, we have
 
 
|-
 
|-
 
|
 
|
 
::<math>\begin{array}{rcl}
 
::<math>\begin{array}{rcl}
\displaystyle{f(x)} & = & \displaystyle{\frac{x^2+x^3}{x}}\\
+
\displaystyle{h'(x)} & = & \displaystyle{(f'\circ g(x))\cdot g'(x)}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{x^2}{x}+\frac{x^3}{x}}\\
+
& = & \displaystyle{8(x+1)^7\cdot 1}\\
 
&&\\
 
&&\\
& = & \displaystyle{x+x^2.} \\
+
& = & \displaystyle{8(x+1)^7.}
 
\end{array}</math>
 
\end{array}</math>
|-
 
|Now, using the Power Rule, we get
 
|-
 
|
 
::<math>f'(x)=1+2x.</math>
 
 
|}
 
|}
  
Line 144: Line 82:
 
!Final Answer: &nbsp;
 
!Final Answer: &nbsp;
 
|-
 
|-
||&nbsp; &nbsp; &nbsp; &nbsp;<math>f'(x)=\frac{x(2x+3x^2)-(x^2+x^3)}{x^2}</math>
+
||&nbsp; &nbsp; &nbsp; &nbsp;<math>h'(x)=8(x+1)^7.</math>
|-
 
|or equivalently
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp;<math>f'(x)=1+2x</math>
 
 
 
|-
 
 
|}
 
|}
  
'''3)''' &nbsp; <math style="vertical-align: -14px">f(x)=\frac{\sin x}{\cos x}</math>
+
'''3)''' &nbsp; <math style="vertical-align: -7px">h(x)=\ln(x^2)</math>
  
 
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Solution: &nbsp;
 
!Solution: &nbsp;
 
|-
 
|-
|Using the Quotient Rule, we get
+
|Let &nbsp;<math style="vertical-align: -5px">f(x)=\ln (x)</math>&nbsp; and &nbsp;<math style="vertical-align: -5px">g(x)=x^2.</math>
 +
|-
 +
|Then, &nbsp;<math style="vertical-align: -13px">f'(x)=\frac{1}{x}</math>&nbsp; and &nbsp;<math style="vertical-align: -5px">g'(x)=2x.</math>
 +
|-
 +
|Now, &nbsp;<math style="vertical-align: -6px">h(x)=f\circ g(x).</math>
 +
|-
 +
|Using the Chain Rule, we have
 
|-
 
|-
 
|
 
|
 
::<math>\begin{array}{rcl}
 
::<math>\begin{array}{rcl}
\displaystyle{f'(x)} & = & \displaystyle{\frac{\cos x(\sin x)'-\sin x (\cos x)'}{(\cos x)^2}}\\
+
\displaystyle{h'(x)} & = & \displaystyle{(f'\circ g(x))\cdot g'(x)}\\
&&\\
 
& = & \displaystyle{\frac{\cos x(\cos x)-\sin x (-\sin x)}{(\cos x)^2}}\\
 
&&\\
 
& = & \displaystyle{\frac{\cos^2 x+\sin^2 x}{\cos^2 x}} \\
 
 
&&\\
 
&&\\
& = & \displaystyle{\frac{1}{\cos^2 x}}\\
+
& = & \displaystyle{\frac{1}{x^2}\cdot 2x}\\
 
&&\\
 
&&\\
& = & \displaystyle{\sec^2 x}
+
& = & \displaystyle{\frac{2}{x}.}
 
\end{array}</math>
 
\end{array}</math>
|-
 
|since &nbsp;<math style="vertical-align: -2px">\sin^2 x+\cos^2 x=1</math>&nbsp; and &nbsp;<math style="vertical-align: -13px">\sec x=\frac{1}{\cos x}.</math>
 
|-
 
|Since &nbsp;<math style="vertical-align: -14px">\frac{\sin x}{\cos x}=\tan x,</math>&nbsp; we have
 
|-
 
|
 
::<math>\frac{d}{dx}{\tan x}=\sec^2 x.</math>
 
 
|}
 
|}
  
Line 184: Line 111:
 
!Final Answer: &nbsp;
 
!Final Answer: &nbsp;
 
|-
 
|-
|&nbsp; &nbsp; &nbsp; &nbsp;<math>f'(x)=\sec^2 x</math>
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math>h'(x)=\frac{2}{x}</math>
 
|-
 
|-
 
|}
 
|}
Line 190: Line 117:
 
== Exercise 1 ==
 
== Exercise 1 ==
  
Calculate the derivative of &nbsp;<math style="vertical-align: -13px">f(x)=\frac{1}{x^2}(\csc x-4).</math>
+
Calculate the derivative of &nbsp;<math style="vertical-align: -6px">h(x)=(\sin x+\cos x)^4.</math>
 
 
First, we need to know the derivative of &nbsp;<math style="vertical-align: 0px">\csc x.</math>&nbsp; Recall
 
 
 
::<math>\csc x =\frac{1}{\sin x}.</math>
 
 
 
Now, using the Quotient Rule, we have
 
 
 
::<math>\begin{array}{rcl}
 
\displaystyle{\frac{d}{dx}(\csc x)} & = & \displaystyle{\frac{d}{dx}\bigg(\frac{1}{\sin x}\bigg)}\\
 
&&\\
 
& = & \displaystyle{\frac{\sin x (1)'-1(\sin x)'}{\sin^2 x}}\\
 
&&\\
 
& = & \displaystyle{\frac{\sin x (0)-\cos x}{\sin^2 x}}\\
 
&&\\
 
& = & \displaystyle{\frac{-\cos x}{\sin^2 x}} \\
 
&&\\
 
& = & \displaystyle{-\csc x \cot x.}
 
\end{array}</math>
 
  
Using the Product Rule and Power Rule, we have  
+
Using the Chain Rule, we have
  
 
::<math>\begin{array}{rcl}
 
::<math>\begin{array}{rcl}
\displaystyle{f'(x)} & = & \displaystyle{\frac{1}{x^2}(\csc x-4)'+\bigg(\frac{1}{x^2}\bigg)'(\csc x-4)}\\
+
\displaystyle{h'(x)} & = & \displaystyle{4(\sin x+\cos x)^3 (\sin x+\cos x)'}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{1}{x^2}(-\csc x \cot x+0)+(-2x^{-3})(\csc x-4)}\\
+
& = & \displaystyle{4(\sin x+\cos x)^3 ((\sin x)'+(\cos x)')}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{-\csc x \cot x}{x^2}+\frac{-2(\csc x-4)}{x^3}.}
+
& = & \displaystyle{4(\sin x+\cos x)^3 (\cos x-\sin x)}.
 
\end{array}</math>
 
\end{array}</math>
  
 
So, we have  
 
So, we have  
::<math>f'(x)=\frac{-\csc x \cot x}{x^2}+\frac{-2(\csc x-4)}{x^3}.</math>
+
::<math>h'(x)=4(\sin x+\cos x)^3 (\cos x-\sin x).</math>
  
 
== Exercise 2 ==
 
== Exercise 2 ==
  
Calculate the derivative of &nbsp;<math style="vertical-align: -5px">g(x)=2x\sin x \sec x.</math>
+
Calculate the derivative of &nbsp;<math style="vertical-align: -6px">h(x)=\sin^3(2x^2+x+1).</math>
  
Notice that the function &nbsp;<math style="vertical-align: -5px">g(x)</math>&nbsp; is the product of three functions.
+
First, notice &nbsp;<math style="vertical-align: -6px">h(x)=(\sin(2x^2+x+1))^3.</math>  
  
We start by grouping two of the functions together. So, we have &nbsp;<math style="vertical-align: -5px">g(x)=(2x\sin x)\sec x.</math>
+
Using the Chain Rule, we have
  
Using the Product Rule, we get
+
::<math>h'(x)=3(\sin(2x^2+x+1))^2 \cdot (\sin(2x^2+x+1))'.</math>
 
 
::<math>\begin{array}{rcl}
 
\displaystyle{g'(x)} & = & \displaystyle{(2x\sin x)(\sec x)'+(2x\sin x)'\sec x}\\
 
&&\\
 
& = & \displaystyle{(2x\sin x)(\tan^2 x)+(2x\sin x)'\sec x.}
 
\end{array}</math>
 
  
Now, we need to use the Product Rule again. So,
+
Now, we need to use the Chain Rule a second time. So, we get
  
 
::<math>\begin{array}{rcl}
 
::<math>\begin{array}{rcl}
\displaystyle{g'(x)} & = & \displaystyle{2x\sin x\tan^2 x+(2x(\sin x)'+(2x)'\sin x)\sec x}\\
+
\displaystyle{h'(x)} & = & \displaystyle{3(\sin(2x^2+x+1))^2 \cos(2x^2+x+1)\cdot (2x^2+x+1)'}\\
 
&&\\
 
&&\\
& = & \displaystyle{2x\sin x\tan^2 x+(2x\cos x+2\sin x)\sec x.}
+
& = & \displaystyle{3\sin^2(2x^2+x+1) \cos(2x^2+x+1)(4x+1).}
 
\end{array}</math>
 
\end{array}</math>
  
 
So, we have  
 
So, we have  
::<math>g'(x)=2x\sin x\tan^2 x+(2x\cos x+2\sin x)\sec x.</math>
+
::<math>h'(x)=3\sin^2(2x^2+x+1) \cos(2x^2+x+1)(4x+1).</math>
  
But, there is another way to do this problem. Notice
+
== Exercise 3 ==
  
::<math>\begin{array}{rcl}
+
Calculate the derivative of &nbsp;<math style="vertical-align: -6px">h(x)=\cos (2x+1)\sin(x^2+3x).</math>
\displaystyle{g(x)} & = & \displaystyle{2x\sin x\sec x}\\
 
&&\\
 
& = & \displaystyle{2x\sin x\frac{1}{\cos x}}\\
 
&&\\
 
& = & \displaystyle{2x\tan x.}
 
\end{array}</math>
 
  
Now, you would only need to use the Product Rule once instead of twice.
+
Using the Product Rule, we have
  
== Exercise 3 ==
+
::<math>h'(x)=\cos(2x+1)(\sin(x^2+3x))'+(\cos(2x+1))'\sin(x^2+3x).</math>
  
Calculate the derivative of &nbsp;<math style="vertical-align: -16px">h(x)=\frac{x^2\sin x+1}{x^2\cos x+3}.</math>
+
For the two remaining derivatives, we need to use the Chain Rule.  
  
Using the Quotient Rule, we have
+
So, using the Chain Rule, we have
 
 
::<math>h'(x)=\frac{(x^2\cos x+3)(x^2\sin x+1)'-(x^2\sin x+1)(x^2\cos x+3)'}{(x^2\cos x+3)^2}.</math>
 
 
 
Now, we need to use the Product Rule. So, we have
 
  
 
::<math>\begin{array}{rcl}
 
::<math>\begin{array}{rcl}
\displaystyle{h'(x)} & = & \displaystyle{\frac{(x^2\cos x+3)(x^2(\sin x)'+(x^2)'\sin x)-(x^2\sin x+1)(x^2(\cos x)'+(x^2)'\cos x)}{(x^2\cos x+3)^2}}\\
+
\displaystyle{h'(x)} & = & \displaystyle{\cos(2x+1)\cos(x^2+3x)\cdot (x^2+3x)'-\sin(2x+1)\cdot (2x+1)'\sin(x^2+3x)}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{(x^2\cos x+3)(x^2\cos x+2x\sin x)-(x^2\sin x+1)(-x^2\sin x+2x\cos x)}{(x^2\cos x+3)^2}.}
+
& = & \displaystyle{\cos(2x+1)\cos(x^2+3x) (2x+3)-\sin(2x+1)(2)\sin(x^2+3x).}
 
\end{array}</math>
 
\end{array}</math>
  
 
So, we get
 
So, we get
::<math>h'(x)=\frac{(x^2\cos x+3)(x^2\cos x+2x\sin x)-(x^2\sin x+1)(-x^2\sin x+2x\cos x)}{(x^2\cos x+3)^2}.</math>
+
::<math>h'(x)=\cos(2x+1)\cos(x^2+3x) (2x+3)-\sin(2x+1)(2)\sin(x^2+3x).</math>
  
 
== Exercise 4 ==
 
== Exercise 4 ==
  
Calculate the derivative of  &nbsp;<math style="vertical-align: -14px">f(x)=\frac{e^x}{x^2\sin x}.</math>
+
Calculate the derivative of  &nbsp;<math style="vertical-align: -16px">h(x)=\frac{\sin(3x)+x\cos(2x)}{x^2+1}.</math>
  
 
First, using the Quotient Rule, we have
 
First, using the Quotient Rule, we have
  
 
::<math>\begin{array}{rcl}
 
::<math>\begin{array}{rcl}
\displaystyle{f'(x)} & = & \displaystyle{\frac{x^2\sin x (e^x)'-e^x(x^2\sin x)'}{(x^2\sin x)^2}}\\
+
\displaystyle{h'(x)} & = & \displaystyle{\frac{(x^2+1)(\sin(3x)+x\cos(2x))'-(\sin(3x)+x\cos(2x))(x^2+1)'}{(x^2+1)^2}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{(x^2+1)[(\sin(3x))'+(x\cos(2x))']-(\sin(3x)+x\cos(2x))(2x)}{(x^2+1)^2}.}
 +
\end{array}</math>
 +
 
 +
Using the Product Rule, we get
 +
 
 +
::<math>\begin{array}{rcl}
 +
\displaystyle{h'(x)} & = & \displaystyle{\frac{(x^2+1)[(\sin(3x))'+x(\cos(2x))'+(x)'\cos(2x)]-(\sin(3x)+x\cos(2x))(2x)}{(x^2+1)^2}}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{x^2\sin x e^x - e^x(x^2\sin x)'}{x^4\sin^2 x}.}
+
& = & \displaystyle{\frac{(x^2+1)[(\sin(3x))'+x(\cos(2x))'+1\cos(2x)]-(\sin(3x)+x\cos(2x))(2x)}{(x^2+1)^2}.}
 
\end{array}</math>
 
\end{array}</math>
  
Now, we need to use the Product Rule. So, we have
+
For the remaining derivatives, we need to use the Chain Rule. So, we get
  
 
::<math>\begin{array}{rcl}
 
::<math>\begin{array}{rcl}
\displaystyle{f'(x)} & = & \displaystyle{\frac{x^2\sin x e^x - e^x(x^2(\sin x)'+(x^2)'\sin x)}{x^4\sin^2 x}}\\
+
\displaystyle{h'(x)} & = & \displaystyle{\frac{(x^2+1)[\cos(3x)(3x)'+x(-\sin(2x))(2x)'+\cos(2x)]-(\sin(3x)+x\cos(2x))(2x)}{(x^2+1)^2}}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{x^2\sin x e^x - e^x(x^2\cos x+2x\sin x)}{x^4\sin^2 x}.}
+
& = & \displaystyle{\frac{(x^2+1)[\cos(3x)(3)-x\sin(2x)(2)+\cos(2x)]-(\sin(3x)+x\cos(2x))(2x)}{(x^2+1)^2}.}
 
\end{array}</math>
 
\end{array}</math>
  
 
So, we have  
 
So, we have  
::<math>f'(x)=\frac{x^2\sin x e^x - e^x(x^2\cos x+2x\sin x)}{x^4\sin^2 x}.</math>
+
::<math>h'(x)=\frac{(x^2+1)[\cos(3x)(3)-x\sin(2x)(2)+\cos(2x)]-(\sin(3x)+x\cos(2x))(2x)}{(x^2+1)^2}.</math>

Latest revision as of 14:20, 15 October 2017

Introduction

It is relatively easy to calculate the derivatives of simple functions, like polynomials or trigonometric functions.

But, what about more complicated functions?

For example,    or  

Well, the key to calculating the derivatives of these functions is to recognize that these functions are compositions.

For    it is the composition of the function    with  

Similarly, for    it is the composition of    and  

So, how do we take the derivative of compositions?

The answer to this question is exactly the Chain Rule.

Chain Rule

Let    be a differentiable function of    and let    be a differentiable function of   

Then,    is a differentiable function of    and

Warm-Up

Calculate  

1)  

Solution:  
Let    and  
Then,    and  
Now,  
Using the Chain Rule, we have
Final Answer:  
       

2)  

Solution:  
Let    and  
Then,    and  
Now,  
Using the Chain Rule, we have
Final Answer:  
       

3)  

Solution:  
Let    and  
Then,    and  
Now,  
Using the Chain Rule, we have
Final Answer:  
       

Exercise 1

Calculate the derivative of  

Using the Chain Rule, we have

So, we have

Exercise 2

Calculate the derivative of  

First, notice  

Using the Chain Rule, we have

Now, we need to use the Chain Rule a second time. So, we get

So, we have

Exercise 3

Calculate the derivative of  

Using the Product Rule, we have

For the two remaining derivatives, we need to use the Chain Rule.

So, using the Chain Rule, we have

So, we get

Exercise 4

Calculate the derivative of  

First, using the Quotient Rule, we have

Using the Product Rule, we get

For the remaining derivatives, we need to use the Chain Rule. So, we get

So, we have